Antiinflammatory and Antimicrobial Activity of Anthraquinone Isolated from Aloe vera (Liliaceae) - Abbas Lone, Mohammad; Malviya, Dinisha; Mishra, Pooja; Dubey, Aarti; Saxena, R.C. (Asian Journal of Chemistry, 2010)
Aloe vera Linn family Liliaceae is known as wonder herb because of its wide medicinal uses. Cell sap of Aloe vera was taken in Petridish and was phytochemically screened for anthraquinone which is phenolic compound found invariably, in sap of fleshy leaves. Anthraquinone 'Emodin' was isolated from the plant sap which show pain killing, antiinflammatory and antimicrobial activity against Staphylococcus aureus strain (MTCC 96).